Comparison of three techniques for appendiceal stump closure during laparoscopy - Gemici, Eyüp; Dönmez, Turgut; Sürek, Ahmet; Abdullayev, Seymur; Aydın, Hüsnü; Bozkurt, Mehmet Abdussamet; Karabulut, Mehmet (Journal of Surgery and Medicine, 2020)
Aim: Laparoscopic appendectomy is the gold standard treatment of acute appendicitis. However, there is no consensus about the technique to apply when closing the appendix stump. This study compares three techniques to close the appendix stump: Laparoscopic purse-string suture (LPS), metal clips, and Hem-o-lok clips. The aim is to evaluate the advantages, safety, and costs of these three methods. Methods: We conducted a retrospective cohort study which included 220 patients who underwent laparoscopic appendectomy operations for acute appendicitis between May 2017 and December 2019. The cases were divided into three groups and evaluated. Group A received LPS, group B received metal clips, and group C received Hem-o-lok clips. The demographic features of the patients, American Society of Anesthesiology (ASA) scores, duration of surgery, postoperative complications, hospital stay, and cost were evaluated retrospectively from patient files. Results: There were 79 patients in group A, 91 patients in group B, and 50 patients in group C. There was no difference between the groups with respect to demographic features, ASA physiological state scores, and laboratuary values. The operation time and postoperative complication rates did not differ between groups (P>0.05). Group C had longer hospital stays (P=0.001), and group A had lower costs (P=0.001). Conclusion: In the laparoscopic appendectomy technique, the use of LPS for appendix stump closure is safe and effective. Furthermore, technical consumables and hospital treatment costs are significantly reduced.